Window blind operations and their relationship with environment factors and occupant's behaviour in a green-certified office building in Malaysia - Alam, S M Jubaer (2019)
There is a need to understand the correlations between window blind operations with the environmental factors and occupants’ behaviour to improve the indoor visual environment and daylight performance of office buildings in Malaysia. Improper positioning and seldom use of window blinds can hamper the penetration of daylight into office buildings, which may cause high electricity consumption and poor indoor visual environment. According to some studies, many of the existing office buildings in Malaysia are consuming high amount of electricity, partly because the occupants leave the window blinds fully lowered and depend on artificial lightings during daytime. Furthermore, the real reasons behind, and the influential factors of, occasional blind operation are still unknown for countries with hot and humid climatic condition. Therefore, this study aims to explore the behaviour of green office building’s occupants regarding their control of window blinds as well as to investigate the manual blind use patterns and their correlations with the building orientations, sky conditions, floor levels and time of the day. The main objectives are, 1) to analyse how and why the office occupants operate their window blinds through a questionnaire survey among occupants; 2) to determine whether building façade orientations, sky conditions, different floor levels, and time of the day, influence the level of occlusion and the frequency of window blinds adjustment; and 3) to examine how window blinds are affecting occupants’ visual comfort level. A GBI Gold-certified office building in Putrajaya was selected as a case study building for this study. This study used time-lapse photography to record the positions of the blinds. A questionnaire survey was also conducted among the building occupants to deepen understanding of their views on window blind operation. The Spearman’s Correlation and ANOVA tests were conducted for the statistical analysis of the blind positions in relation to the different environmental factors. The responses obtained from the survey were analysed using descriptive and cross-tabulation analyses. The Spearman’s Correlation and ANOVA tests revealed that the positioning and movements of the window blinds were correlated with the building orientations and floor levels and sometimes with the sky conditions. However, no relationship was found between the window blind operation and time of the day. The survey results revealed that most of the occupants did not operate their window blinds frequently, and glare from the daylight and outside views were the two main reasons for closing and opening their blinds respectively. The results indicate that there was a lack of willingness among occupants to operate their window blinds frequently throughout the day, which may result in poor daylight condition and high dependency on the artificial lightings. It is expected that findings of this study will contribute to further studies on window blind operation involving more office buildings in the tropics to ensure good indoor visual environment. It is hoped that this study will help to raise awareness among building occupants and encourage them to operate their window blinds frequently to better utilise the available daylight and to reduce the usage of artificial lightings.